The determinants of murabaha margin income in Islamic banking companies in Indonesia - Musaroh Musaroh; Naning Margasari; Nindya Nuriswati Laili; Mahendra Ryansa Gallen Gagah Pratama (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2020)
This research was conducted to examine the effect of the operational costs, third-party funds, murabaha financing volume, Bank Indonesia’s interest rate and inflation on murabaha margin income at Islamic commercial banks in Indonesia. The period used in this research is 3 years, from 2016 to 2018. This study's population were 14 Islamic commercial banks that have been and are still registered with the Financial Services Authority from 2016 to 2018. The sampling technique used was purposive sampling and obtained a sample of 9 Islamic commercial banks. The data analysis technique used is multiple linear regression. Before conducting the multiple linear regression analysis, a classic assumption test was carried out to ensure that the model did not have normality, heteroscedasticity, autocorrelation, and multicollinearity. The results show that partially operational costs have a positive and significant effect on murabaha margin income, third-party funds have a negative and significant effect on murabaha margin income, murabaha financing volume has a positive and significant effect on murabaha margin income, while the Bank Indonesia’s interest rate and inflation do not influence on Murabaha margin income.